Uma revis?o sistem?tica sobre a abordagem geom?trica no ensino de fun??es quadr?ticas - Bonfim, Cez?rio Silvino (2019)
Since the Mathematical discipline was introduced in the curriculum of Secondary Education in the early 21st Century from the fusion of Algebra, Geometry and Arithmetic, Function content has played the role of connecting the knowledge coming from these three pillars of mathematical knowledge. However, the historicity of the function teaching approach points to a progressive distancing from the unifying role attributed to functional thinking. Among the various cognitive and epistemological drawbacks, there is an exaltation of the algebraic approach over the geometric approach, which we conjecture as essential for the development of mathematical knowledge. Among the various types of functions addressed in high school, the quadratic function is the most studied by students, along with the 1o polynomial function, appearing in the most diverse contexts of explanation of mathematical knowledge. This paper synthesizes the methodological trends of quadratic function teaching and makes an analysis of teaching strategies that uses the geometric approach to consolidate functional thinking. For this, we used the systematic literature review, which points out that geometry has been recurrent in studies that propose innovative strategies for teaching quadratic functions and that strategies in which a geometric approach is not relevant approach the traditional teaching proposals